Counter-terrorism and counter-law: an archetypal critique. (22nd June 2018) - Edwards, Phil
Abstract: Contemporary British counter-terrorist legislation is dominated by 'counter-law' in Richard Ericson's terms: by using law against law, it systematically undermines the rule of law. This paper supports this proposition by developing a detailed 'archetypal' account of the rule of law considered as a critical ideal, drawing on Fuller's 'morality of law'. The rule of law is identified with four tendencies in law – towards greater universality, knowability, followability and justifiability – and 'counter-law' with tendencies to block or reverse all of these. Counter-law tendencies in contemporary counter-terrorist legislation are discussed in detail, with particular reference to the proliferation of inchoate, preparatory and situational offences. This critique is also related to contemporary debates on law and counter-law; it is argued that critiques which relativise or historicise the liberal model of the rule of law fall short by failing to engage with it on its own terms, thereby undervaluing its utility as a normative resource. The paper concludes by discussing the range, significance and gravity of the departures from the rule of law that have been identified, considering some counter-arguments and drawing conclusions for policy-makers and legal scholars.